2019
DOI: 10.1161/circheartfailure.118.005552
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of Intensive Volume Removal in Heart Failure Patients With Preexisting Worsening Renal Function

Abstract: Background:The relationship between intensive volume removal in ADHF patients with preexisting WRF and renal tubular injury, post-discharge renal function, and clinical outcomes is unknown. Methods and Results:We used data from the multicenter CARRESS-HF trial that randomized patients with ADHF and pre-existing WRF to intensive volume removal with stepped pharmacologic therapy (SPT) or fixed rate ultrafiltration (UF). Patients in the urinary renal tubular injury biomarker sub-study (NAG, KIM-1, and NGAL) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 37 publications
2
32
0
2
Order By: Relevance
“…Furthermore, increases in kidney injury markers were paradoxically associated with better outcomes. Similar results were recently reported when the same biomarkers were measured in 105 patients in the CARRESS‐HF cohort, a population of patients already experiencing significant WRF . Notably, patients who had a rise in injury biomarkers were more likely to have an improvement in creatinine at 60 days after enrolment.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, increases in kidney injury markers were paradoxically associated with better outcomes. Similar results were recently reported when the same biomarkers were measured in 105 patients in the CARRESS‐HF cohort, a population of patients already experiencing significant WRF . Notably, patients who had a rise in injury biomarkers were more likely to have an improvement in creatinine at 60 days after enrolment.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, increases in kidney injury markers were paradoxically associated with better outcomes. Similar 25 Notably, patients who had a rise in injury biomarkers were more likely to have an improvement in creatinine at 60 days after enrolment. AKINESIS adds to these studies because its population represents the largest cohort studied and its results are in line with those of the latter studies in finding that uNGAL does not predict long-term adverse outcomes.…”
Section: Discussionmentioning
confidence: 57%
“…However, post hoc analysis of the data showed that patients who had worsening kidney function during the intervention period had better kidney function at 60 days, regardless of treatment group. 9 These studies suggest that AKI, defined by small to moderate increases in Scr, is not a valid proxy for PCOs in acute decompensated heart failure. In this clinical setting, a modest increase in Scr could reflect adequate decongestion rather than an adverse event.…”
Section: Mild Aki and Pcosmentioning
confidence: 95%
“…showed that in a subgroup of 283 patients from the ROSE‐AHF trial treated with aggressive diuresis elevation, uNGAL as well as two other urinary AKI biomarkers, N‐acetyl‐β‐d‐glucosaminidase (NAG) and kidney injury molecule 1 (KIM‐1), were paradoxically associated with reduced post‐discharge 180‐day all‐cause mortality (adjusted hazard ratio 0.80 per 10 percentile increase, P = 0.001). Rao et al . also demonstrated that patients developing elevation of uNGAL during the first 4 days of ADHF treatment had paradoxically better recovery of kidney function (adjusted odds ratio 6.3, P < 0.001) in a subgroup of 105 patients from the CARRESS‐HF trial.…”
mentioning
confidence: 97%
“…AHF occurs in patients with heterogeneous baseline characteristics; therefore, NGAL may not be able to characterize the risk of AKI across different co‐morbid conditions. Nonetheless, biomarker studies in AHF contributed to the discovery that not all cases of WRF are associated with the increase in traditional AKI biomarkers and that elevations of AKI biomarkers are not always associated with worse outcomes . Ahmad et al .…”
mentioning
confidence: 99%